Karyotype analysis of Schizochytrium mangrovei PQ6 using dapi (4, 6-diamidino-2-phenylidole) counterstaining and pulsed-field gel electrophoresis (pfge) techniques - Lan Anh, Hoang Thi; Hoai Thu, Ngo Thi; Hoang, Tran Huy; Zhou, ZhiGang; Que, Tran; Ha, Chu Hoang; Hai, Truong Nam; Hong, Dang Diem (Academia Journal of Biology, 2015)
Schizochytrium mangrovei PQ6 is a heterotrophic marine microalga which was isolated from Phu Quoc Island, Kien Giang province. It has many unique characteristics, including ability to be adapted to varying culture environmental conditions, such as temperature, salinity, pH as well as producing high biomass (30-40 g of dry cell weight - DCW per liter), lipid content (up to 70% DCW), and especially rich in polyunsaturated fatty acids, such as docosahexaenoic acid-DHA, C22: 6n-3; eicosapentaenoic acid-EPA, C20: 5n-3, docosapentaenoic acid-DPA, C22: 5n-6. The biomass of this strain was studied to use for aquaculture feed, functional food, biodiesel and some bioactive compounds (polyunsaturated fatty acid, squalene) production. However, until now no scientific reports published in the world pertaining karyotype analysis of this species as well as others species belonging to the genus Schizochytrium. In this paper, for karyotype analysis experiment, we used colchicine to arrest the cell cycle at the metaphase. To obtain clear images, the cells of PQ6 strain were treated with maceration enzymes and chromosomes were stained with DAPI (4’, 6-diamidino-2-phenylindole) and observed under fluorescence microscopy. The experimental results showed that PQ6 strain has three chromosomes. On the other hand, four bands (equal four chromosomes) were separated by pulsed-field gel electrophoresis (PFGE). The different of obtained number of chromosome allowed us to suggest that maybe, this microalga has a plasmid. And thus, this question needs to be clarified in the near future. However, the result of our research provides first evidence about karyotype and served as an initial basic for genomic assembly and annotation of this microalga.